Perencanaan Arsitektur Enterprise Desa Cerdas dengan Togaf 10: Dimensi Hidup Cerdas - Pasaribu, Magdalena Edelways Enjelina; Fajrillah, Asti Amalia Nur; Nurtrisha, Widyatasya Agustika (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
The application of the smart village concept is an adaptation of smart cities designed to improve the quality of life in rural areas by adjusting local needs and characteristics. Smart Village development aims to transform villages through information technology with an active community role approach and cooperation to improve the quality of village development according to the six pillars of Smart Village and accelerate the achievement of Sustainable Development Goals (SDGs). The research focuses on designing enterprise architecture for the smart village concept in the smart living dimension focusing on SDGs Village Goal 2 (Zero Hunger Village) in Sindangpanon Village. The assessment of the achievement of SDGs Village Goal 2 (Zero Hunger Village) is still quite low at 33.33. Overcoming this problem requires designing enterprise architecture using the TOGAF 10 framework which consists of Preliminary Phase, Architecture Vision, Business Architecture, Data Architecture, Application Architecture, Technology Architecture, Opportunities and Solutions, and Migration Planning. The output of this research, namely Enterprise Architecture blueprint, will help the government improve the effectiveness and efficiency of village services and support community welfare.